Belarusian Nationalism: Taking Stock of Its Accomplishments - G. Ioffe (Международная аналитика, 2021)
Belarus is a country with a blurred identity that has not cut the umbilical cord connecting it with Mother Russia. According to a representative national survey of April 2020, only 25 percent of Belarusians would prefer to retain statehood and national sovereignty of Belarus even if their living standards worsen whereas 52 percent would opt for limited sovereignty if it is the price to pay for retaining or improving the quality of life. This may be the best-kept secret of Belarus and it has implications more serious than just economic dependency on Belarus’s eastern neighbor. Belarus used to be a contested borderland claimed by both Russians and Poles. Today, it is a country with two historical narratives and nation-building blueprints that have been confronting each other since the inception of the Belarusian national movement. While the neo-Soviet/Russo-centric narrative has held sway over the majority of Belarusians, the Westernizing narrative was hard-hit on several occasions but has been making headway since Gorbachev’s Perestroika. Pluses and minuses of two narratives and the attempts at bridging the gap between them are analyzed. There are essentially two kinds of divisions in Belarusian society: between the respective projects of nation-building and between Lukashenka loyalists and his detractors. These two divisions do not quite coincide, but there is a growing tendency to couch the ongoing political crisis in nationalist terms. The point is made that a lack of cohesive Belarusian identity is an existential threat to Belarusian statehood.